Best Practice of Construction Waste Management and Minimization - Khor, Jie Cheng; Othuman Mydin, Md Azree (Eftimie Murgu University of Resita, 2014)
Material management is an important issue as seen in construction waste management. Best practice of material management is accompanied by various benefits which are acknowledged by several studies. The site layout has particular effects on both materials and their waste through effective waste management practice. Ignoring the benefits of material management could result in a daily reduction in productivity of up to 40% by material wastage. Thus, the benefits of effective material management must be well comprehended for the sake of waste minimization. Another convincing fact about waste is that poor site management accounts for the largest factor of waste generation. Hence the site condition is very crucial in developing effective material management. Factors contributing to the efficiency of material management process are effective logistical management and supply chain management. The logistics system must be performing as schedule so that materials are wisely managed on-site without encountering presence of excessive materials. As materials management is closely related to logistics in construction projects, there will be delay in construction projects when materials are not delivered to site as scheduled. The management must be effective in terms of delivery, off-loading, storage, handling, on-site transportation and on-site utilization of materials.